Global Campus Consortia - Jorge L., Díaz-Herrera (VNU Journal of Science: Social Sciences and Humanities; Vol 31 No 4, 2015)
The business of colleges and universities is the business of ideas through the creation of new knowledge by way of research and the dissemination of this knowledge through education. In today’s world, we need to talk about the global circulation of ideas. The internationalization of education is an institutional imperative and global learning and exploration is a reality. U.S. institutions of higher education have come a long way since only a decade or so ago when just a few research universities were talking about international exchanges. Although we are witnessing a surge in the creation of international, multifaceted educational partnerships, a strategic trend for colleges and universities, but today many institutions are still lagging behind or just beginning to understand its importance. In this paper, we focus on the need and requirements, as well as challenges and opportunities for creating dynamically active international consortia as a force to further international education throughout the world that is not confined to simply faculty and student exchanges or degree completion programs, but the true global circulation of ideas. The purpose of global campus consortia is to facilitate the global circulation of ideas, whereby students and faculty among its members can participate freely and smoothly in all exchanges. That is, to the free movement of students and faculty as well as course credits among institutions and across geographical boundaries.